DAYA DUKUNG HIJAUAN DAN LIMBAH TANAMAN PANGAN PENGEMBANGAN POPULASI TERNAK SAPI POTONG DI KECAMATAN TOMPASO KABUPATEN MINAHASA - Erwin Wantasen; S. Dalie; F.N.S. Oroh (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2016)
Farm development showed a good prospect and has an important role in the growth of the agricultural economy. The problem is how far the supported of land resources, can increase the cattle population in Tompaso district of Minahasa regency. Based on this problems the study was applied. The aimed of the research was to know potensial development of cattle in Tompaso sub district Minahasa regency based on the availability of forages and agriculture by product. Secondary data analysis methods was used to meet the objectif of the research such as planted area used by the farmers and population of cattle in Tompaso sub district. The data was collected from extension office of agriculture , fisheries and forestry (BP3K) and agriculture service of Minahasa regency. Potensial livestock development analysis was used to find out the goal of the research. Result of this study showed the effectif forages production were 1.811,86 ton p.a. Effectif production of agriculture by product was 6.630,39 ton p.a. Maximum carrying capacity of Tompaso sub district were 4.020,11 animal unit. Capacity increase of cattle population by land resources ( KPPTR) were 1.459,65 animal unit. Based on the research, Tompaso sub district has carrying capacity as developing area of cattle in Minahasa Regency North Sulawesi. Keywords : cattle , carrying capacity, forages , agriculture by product